Cultural variations and business performance contemporary globalism - Christiansen, Bryan, 1960- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book offers the latest research in the field of Business Performance Management in the global economic environment of present conditions while looking at business as a whole entity instead of only at the divisional level"--Provided by publisher.